2009
DOI: 10.1097/prs.0b013e3181904d3a
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Neurotization: A Novel Solution to Neurotrophic Keratopathy

Abstract: Direct neurotization of the cornea using the contralateral supraorbital and supratrochlear branches of the ophthalmic division of the trigeminal nerve appears to be an effective method of restoring the corneal sensibility in patients with unilateral facial palsy and anesthetic cornea. This technique preserves ocular anatomy and cosmesis and restores function by improving corneal health and visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
2
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(195 citation statements)
references
References 15 publications
2
185
2
6
Order By: Relevance
“…In this study, the aesthetic Plastic and Reconstructive Surgery • October 2009 outcome was assessed after the completion of all procedures (including secondary) and, although no grading was performed immediately before the secondary procedures for comparison, our previous studies demonstrated a clear benefit. [15][16][17][18] Eyelid Closure Three patients (16.6 percent) had muscle transfer for dynamic restoration of eye closure (Fig. 5), whereas corrections were made by means of a palpebral spring, gold weight, or lower lid minitendon graft in another eight patients (Tables 6 through 8), at the second stage of the babysitter procedure or later.…”
Section: Secondary Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the aesthetic Plastic and Reconstructive Surgery • October 2009 outcome was assessed after the completion of all procedures (including secondary) and, although no grading was performed immediately before the secondary procedures for comparison, our previous studies demonstrated a clear benefit. [15][16][17][18] Eyelid Closure Three patients (16.6 percent) had muscle transfer for dynamic restoration of eye closure (Fig. 5), whereas corrections were made by means of a palpebral spring, gold weight, or lower lid minitendon graft in another eight patients (Tables 6 through 8), at the second stage of the babysitter procedure or later.…”
Section: Secondary Proceduresmentioning
confidence: 99%
“…In our series, apart from eye closure, the lack of corneal sensibility was addressed by performing a novel procedure-direct neurotization of the cornea by means of the contralateral supraorbital and supratrochlear nerves-with gratifying outcomes. 17 For static reconstruction of lagophthalmos and paralytic ectropion, the senior author frequently uses palpebral springs, 15 gold weights, 15 or minitendon grafts. 16 The free muscle transfer remains the cornerstone in the reconstruction of paralyzed smile.…”
Section: Plastic and Reconstructive Surgery • October 2009mentioning
confidence: 99%
“…In this group, eight pedicled frontalis transfers, three pedicled temporalis transfers, four free platysma transfers, two free gracilis subunits transfers, one free extensor digitorum brevis transfer, one free occipitalis transfer, and one free adductor longus transfer were performed. Six corneal neurotization procedures 31 were also included in this study (Table 4).…”
Section: Study Groupsmentioning
confidence: 99%
“…This could be compensated for with inclusion of the ST nerve in the transfer. Terzis et al 23 reported the use of SO and ST nerves transfer for corneal neurotization in facial paralysis. Through a bicoronal approach, the SO and ST nerves were harvested and implanted in the contralateral cornea for sensory neurotization meaning that the ST nerve would also reach to the ipsilateral IO nerve if necessary .The numbness that resulted from this procedure, called donor deficit, resolved on average within 3 months, and the patients only complained about transient discomfort and itching at the donor site.…”
Section: Discussionmentioning
confidence: 98%